Feeding the world, preventing poverty, and protecting the earth: a 2020 vision - International Food Policy Research Institute (International Food Policy Research Institute, 1996)
This booklet presents eleven stories to show how the broad and often abstract concepts of hunger, poverty, and environmental damage are tragically real when applied to the lives of individuals. It then proposes solutions for improving the lives of these people and millions of others by the year 2020 ...--P. [2] of cover.; A 2020 booklet